Strategi Penyusunan Layout Toko Elektronik untuk Meningkatkan Kenyamanan Pelanggan - Ramadhani, Melda Aulia; Rinaldi, Muhammad (Jurnal Pemberdayaan Umat, 2024)
Purpose: This research aims to analyze the store layout of Crystal Elektronik to evaluate the effectiveness of its current design and propose improvements to enhance customer comfort and operational efficiency. Methodology/approach: The methods used include direct observation, in-depth interviews with the store owner, photographic documentation of the current store layout, and visual layout mapping created using simple graphic design software. Results/findings: The results indicate that Crystal Elektronik employs a grid layout, which generally supports operational effectiveness and facilitates customer ease in locating products. However, several limitations were identified, including narrow spacing between shelves and disorganized product arrangements in the back of the store. The community service team proposed a new layout design involving adjustments to aisle spacing, rearrangement of large electronic items, and optimization of warehouse utilization to address these issues. Conslucions: An effective store layout enhances both customer comfort and operational efficiency. While the current grid layout supports navigation, spatial constraints and disorganization reduce its overall effectiveness. Proposed improvements, such as wider aisles and better product arrangement, can significantly enhance the shopping experience. This study highlights the importance of layout optimization in retail management. Limitations: This research is limited to a single store, which reduces the generalizability of its findings. Contribution: This study contributes to the fields of operations management and retail management, particularly in the area of store layout design. It provides practical insights for retail business practitioners, emphasizing the importance of layout optimization to improve customer comfort and overall business efficiency.